2016
DOI: 10.1007/s40865-016-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult Life Adjustment of Vulnerable Youths. The Relationship Between Criminal History, Employment History and Adult Life Outcomes

Abstract: Purpose This article examines adult outcomes of vulnerable youths. Methods The sample consists of 251 boys and girls who were institutionalized in a Dutch juvenile justice institution in the 1990s. Information on personal and childhood characteristics was extracted from treatment files that were compiled during their stay in the institution. In addition, conviction data was used to determine subjects' criminal careers. Conducting face-to-face interviews with these former JJI detainees when they were on average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
(50 reference statements)
2
12
0
Order By: Relevance
“…Of the 499 men and women we were able to approach, 251 agreed to an interview, resulting in a 50.3% response rate. Non-response analysis in which responders and non-responders were compared on a range of background and current characteristics revealed that the subsample is generally representative of the original sample (for more information, see Van der Geest, Bijleveld & Verbruggen, 2013;Verbruggen et al, 2016).…”
Section: Samplementioning
confidence: 99%
See 4 more Smart Citations
“…Of the 499 men and women we were able to approach, 251 agreed to an interview, resulting in a 50.3% response rate. Non-response analysis in which responders and non-responders were compared on a range of background and current characteristics revealed that the subsample is generally representative of the original sample (for more information, see Van der Geest, Bijleveld & Verbruggen, 2013;Verbruggen et al, 2016).…”
Section: Samplementioning
confidence: 99%
“…In earlier work on the 17up sample, group-based trajectory modelling had been used to estimate offending trajectories from ages 18 to 34 (Verbruggen et al, 2016), and these offending trajectories are used in the current study as well. As discussed in Verbruggen et al (2016), officially registered data on convictions, retrieved from the judicial documentation abstracts of the Netherlands Ministry of Security and Justice, was used.…”
Section: Criminal Behaviourmentioning
confidence: 99%
See 3 more Smart Citations